Heisenberg-Type Families in Uq(sl₂) - Zuevsky, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
Using the second Drinfeld formulation of the quantized universal enveloping algebra Uq(sl₂) we introduce a family of its Heisenberg-type elements which are endowed with a deformed commutator and satisfy properties similar to generators of a Heisenberg subalgebra. Explicit expressions for new family of generators are found.